The Observational Microeconomics Study of the Phenomenon of Entrepreneur Resilience and Collaborative Innovative Financial Leadership in the United States - Eric Brown; Karina Kasztelnik (Financial Markets, Institutions and Risks)
The main purpose of the research is to complete the observation of the phenomenon of entrepreneur resilience and collaborative innovative financial leadership in the United States. Starting a new business is a demanding, and stressful process creating significant changes in a business owner’s life (Yang & Danes, 2015). Due to the financial crisis in 2007-2008, chapter 9 bankruptcy in 2013, and the current insufficiency of jobs in Detroit, Michigan, many individuals had to start their microbusiness. Detroit, Michigan suffered the most extensive municipal bankruptcy filings in American history with a debt estimation close to twenty billion dollars (Washburn, 2015). The methodology is the observation all current and prior existing literature and facts available for the purpose of understanding the current phenomenon of entrepreneur financial innovation leadership. Many entrepreneurs did not have a choice but to start their own business in Detroit, Michigan. Today, entrepreneurs are stressed out, because of the lack of resources needed to provide for themselves and their families while striving to grow their business. If entrepreneurs are not resilient and innovative leadership, they will not survive. This research study confirms and theoretically proves that there is a strong need for microbusiness owners to gain more insight into the relationship between entrepreneur resilience and financial innovation leadership to survive and grow their business. Winterhalter et al. (2016) stated that smaller firms lack the resources of larger organizations to invest in financial innovation leadership to grow their business. Smallbone et al. (2012) stated that small businesses are commonly considered less resilient than larger businesses due to lack of resources, bargaining power, and are unable to spread risk across a large customer base. The critical review study can be useful for the entrepreneurs around the globe.